A Systematic Literature Review: Restorative Justice Approaches Resolving Violations of Electronic Information and Transaction Laws in Indonesia - Edgar Irvin Raranta (Syntax Corporation Indonesia, 2024)
The evolution of society into the information era, propelled by globalization and technological advancements, has transformed social behaviors and interactions, giving rise to the concept of an